La pêche migrante au Sénégal, en Mauritanie et Gambie : un mécanisme d’approvisionnement des industries de farine de poisson - El hadj Bara Dème; Pierre Failler (VertigO)
The objective of the paper is to evaluate the quantitative contribution of the catches of migrant fishers to the supply of fish meal factories in Senegal, The Gambia and Mauritania. The method consisted first of identifying and quantifying the volumes of catches of migrant fishers targeting small pelagics in the three countries studied. Then, field interviews with migrant fishers and fishmongers allowed to determine the share of the catches allocated to the fishmeal industries. On the basis of the fish/fishmeal conversion ratio, the quantity of fishmeal produced from the supply of the migrant artisanal fishermen is determined. Overall, the catches of the four migrant small pelagic fishing chains (three Senegalese and one Guinean) identified in Mauritania and The Gambia are estimated at more than 300,000 tons. More than 72% of this estimated tonnage, i.e. 220,000 tons, is destined to supply the fishmeal factories of the three countries. More than two-thirds of this supply goes to Mauritanian fishmeal factories, with Senegal and The Gambia sharing the remaining third. In addition, of the 500,000 tons of pelagic fish processed annually in fishmeal factories, more than half is supplied by migrant fishermen. At the microeconomic level, the fishmeal industries generate an improvement in the operating accounts of the fisheries, as they ensure the sale of the catches at more remunerative prices than on the local market. However, analyzed on a larger scale, the fishmeal industries create real tensions on the food security of West African countries, knowing that small pelagics constitute the main source of animal protein in Senegal and Gambia, where they have been overexploited for some years now. In addition, they deprive access to artisanal processing of their raw material. All these elements raise the question of the urgent need to regulate the catches of migratory fisheries at the regional level and to drastically reduce the share allocated to the processing of fishmeal for the benefit of local consumption.